Chapter Old Russian Translation of Cosmographia, sive De Situ Orbis by Pomponius Mela: Reception of Renaissance Culture in Muscovy (15th-17th Centuries) - Matasova, Tatiana (Biblioteca di Studi Slavistici, 2020)
The article deals with the results of the analysis of the Old Russian translation of the First book of Cosmographia by Pompons Mela. Mela's Cosmographia was admired and praised by humanists. The research of the way the text was comprehended and interpreted in Muscovy demonstrates the original features of the perception of the Renaissance traditions, ideas and values by Russian intellectuals. The study reveals that the comprehension of Mela's information was characterized by traditional manner of pursuit of biblical analogy. Thus, even the close acquaintance with the Renaissance culture did not change the essence of the Russian Medieval Orthodox culture.